THE EFFECT OF INTERNAL AND EXTERNAL MECHANISM ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Astrid Rudyanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Corporate social responsibility disclosure should be controlled by internal and external mechanism to make sure that company is doing its business morally. Board of commissioners are responsible for supervising company from internal. This study uses board (of commissioner) diversity as internal mechanism. Board diversity is measured by board size, women on board , and board tenure. Public visibility acts as external mechanism to watch corporate social responsibility disclosure. Public visibility is measured by firm size, profitability, and listing age. Corporate social responsibility disclosure is measured using content analysis made by Sembiring (2005). This study aims to examine the effect of board diversity and public visibility on corporate social responsibility disclosure. Using 177 manufacturing companies listed in Indonesia Stock Exchange in the period of 2013-2015, the result shows substitution association of internal and external mechanism on corporate social responsibility disclosure. This shows that one of those mechanisms is enough to increase corporate social responsibility disclosure and regulator shall consider external mechanism for making regulation on internal mechanism. Keywords: board diversity, corporate social responsibility disclosure, external mechanism, internal mechanism, public visibility